A Simplified Model of Adenine-Induced Chronic Kidney Disease Using SKH1 Mice - Benjamin W. French; Joshua D. Breidenbach; Shereen G. Yassine; Bella Z. Khatib-Shahidi; Sara Kazmi; Caitlin M. Murphy; Humza S. Bashir; Evan M. Benson; Bivek Timalsina; Upasana Shrestha; Dhilhani Faleel; Satkeerth Boyapalli; et al. (Cells, 2024)
Commonly used adenine-induced chronic kidney disease (CKD) murine models often employ C57BL/6 mice; however, this strain has inherent limitations due to its natural resistance to developing key pathological features of CKD, such as tubulointerstitial fibrosis and inflammation. There have been attempts to overcome these barriers by using multiple concentrations of adenine-supplemented diets or by performing prolonged experiments up to 20 weeks. Here, we demonstrate that SKH1 Elite mice develop clinically relevant CKD phenotypes (e.g., polyuria, proteinuria, inflammation, and renal fibrosis) over the course of only 6 weeks of low-dose (0.15%) adenine supplementation. As a docile, immunocompetent, and hairless strain, SKH1 Elite mice offer several logistical advantages over C57BL/6 mice, including ease of handling and the ability to study dermal conditions, which are often secondary to CKD.